Laboratory tests on the strengthening of wet-mix shotcrete lining with the use of nanomaterials (Rudarsko-geološko-naftni zbornik, 2021)
Adding nanomaterials to concrete extends the size range of constituent particles well into nano-scale dimensions, which could help the compacting of particles in cement-based materials. Regarding the differences between shotcrete and cast concrete, in this study, the properties of shotcrete with nano and micro-silica and nano-clay were experimentally studied. The micro and nanomaterials have been added at different percentages (6%, 9%, and 12%) to a shotcrete paste. The comparison was based on the uniaxial compressive strength, flexural strength, tensile strength, and porosity tests of different specimens. The results indicated that the maximum increase in compressive, flexural, and tensile strengths of shotcrete was related to 12% nano-SiO2, while for 12% nano-clay, all of these strengths were decreased at 28 days. The optimum percentage for shotcrete substitution by nano-clay was established to be 6%. Also, the application of the nanomaterials led to a decrease in the water absorption and porosity of shotcrete. Eventually, the results revealed that the improvement of mechanical properties by the introduction of the nanomaterials in shotcrete could be satisfactory.